2006
DOI: 10.1130/b25876.1
|View full text |Cite
|
Sign up to set email alerts
|

Cenozoic exhumation of the northern Sierra Nevada, California, from (U-Th)/He thermochronology

Abstract: Apatite and zircon (U-Th)/He ages from a 100-km-long range-perpendicular transect in the northern Sierra Nevada, California, are used to constrain the exhumation history of the range since ca. 90 Ma. (U-Th)/He ages in apatite decrease from 80 Ma along the low western range fl anks to 46 Ma in the higher elevations to the east. (U-Th)/He ages in zircon also show a weak inverse correlation with elevation, decreasing from 91 Ma in the west to 66 Ma in the east. Rocks near the range crest, sampled at elevations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
76
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(83 citation statements)
references
References 63 publications
6
76
1
Order By: Relevance
“…Thermochronologic studies have shown that an ancestral Sierra was uplifted (i.e., surface uplift) during the late Cretaceous to earliest Cenozoic, followed by much lower rate of uplift in the middle to late Cenozoic (Dumitru, 1990;House et al, 1997House et al, , 1998House et al, , 2001Cecil et al, 2006). This two-phase uplift history is seen throughout the Sierra from the Kern River to the American River (Cecil et al, 2006).…”
Section: Regional Settingmentioning
confidence: 93%
“…Thermochronologic studies have shown that an ancestral Sierra was uplifted (i.e., surface uplift) during the late Cretaceous to earliest Cenozoic, followed by much lower rate of uplift in the middle to late Cenozoic (Dumitru, 1990;House et al, 1997House et al, , 1998House et al, , 2001Cecil et al, 2006). This two-phase uplift history is seen throughout the Sierra from the Kern River to the American River (Cecil et al, 2006).…”
Section: Regional Settingmentioning
confidence: 93%
“…Exemplary studies have been conducted in the North American Cordillera (Batt et al, 2001;Benowitz et al, 2011;Cecil et al, 2006;Colgan et al, 2008;Farley et al, 2001;Fitzgerald et al, 1995;Hacker et al, 2011;Spotila et al, 2001), the Andes (Barnes et al, 2008;Gunnell et al, 2010;Insel et al, 2010;Schildgen et al, 2007Schildgen et al, , 2009Schildgen et al, , 2010Spikings et al, 2010), the Southern Alps of New Zealand (Batt et al, 2000;Shuster et al, 2011;Kamp, 1993, 1995), and the Himalayan-Tibetan orogenic system (Kirby et al, 2002;Ouimet et al, 2010;Wobus et al, 2008;Zeitler et al, 2001).…”
Section: Reconstructing Regional Patterns Of Deformation and Erosionmentioning
confidence: 99%
“…Evidence for these conclusions came from tilted Tertiary sedimentary units on the western flanks of the Sierra Nevada and the development of angular unconformities that suggest post-5-Ma range-wide tilting of a rigid Sierra block resulting in up to 2 km of surface uplift of the Sierra Nevada crest (19). A major phase of Pliocene (Ϸ3-5 Ma) surface uplift contrasts results of stable isotope (15,16), thermochronological (23)(24)(25), cosmogenic nuclide (26), and numerical modeling studies (27) that conclude that the modern orographic barrier of the Sierra Nevada has been a long standing topographic feature of the landscape in the western United States. In summary, these studies conclude that crustal thinning during Basin and Range extension could be held responsible for even an elevation loss since the late Miocene (28) and suggest that a Sierra Nevada rain shadow has been in place since that time (15).…”
mentioning
confidence: 99%